An Activatable 19F MRI Molecular Probe for Sensing and Imaging of Norepinephrine. Issue 7 (28th June 2022) - Li, Lingxuan; Li, Ao; Lin, Yaying; Chen, Dongxia; Kang, Bilun; Lin, Hongyu; Gao, Jinhao
Abstract: Norepinephrine (NE), acting as both a neurotransmitter and hormone, plays a significant role in regulating the action of the brain and body. Many studies have demonstrated a strong correlation between mental disorders and aberrant NE levels. Therefore, it is of urgent demand to develop in vivo analytical methods of NE for diagnostic assessment and mechanistic investigations of mental diseases. Herein, we report a 19 F MRI probe (NRFP ) for sensing and imaging NE, which is constructed by conjugating a gadolinium chelate to a fluorine‐containing moiety through a NE‐responsive aromatic thiocarbonate linkage. The capacity and specificity of NRFP for detecting NE is validated with in vitro detecting/imaging experiments. Furthermore, the feasibility of NRFP for visualizing NE in animals is illustrated by ex vivo and in vivo imaging experiments, demonstrating the promising potential of NRFP for selective detection and specific imaging of NE in deep tissues of living subjects. Abstract : A small‐molecular 19 F MRI probe (NRFP) was developed by conjugating a fluorine‐containing moiety and a paramagnetic Gd chelate through a NE‐responsive aromatic thiocarbonate linkage, which allows for detection of NE using 19 F NMR/MRI. Its capacity and specificity for sensing and imaging NE have been demonstrated by a series of in vitro, ex vivo, and in vivo experiments.